Altered cognition in patients following pulmonary embolism - Jia, Shuying; Sun, Chunyan; Xiong, Xingquan; Liu, Xin; Wang, Fang; Liu, Yuyan; Li, Jinling; Zhao, Lei (Frontiers in Medicine, 2026)
BackgroundAcute pulmonary embolism (PE) is a critical disease and often leads to high mortality and morbidity. Growing studies have identified the diagnosis and treatment of PE, but the cognitive situation of PE patients remains unclear. This study investigates cognitive the status in patients with PE and proposes potential lung-brain interaction mechanisms and clinical implications.MethodsWe enrolled 400 adult patients aged > 18 years, diagnosed with acute PE and 91 matched healthy controls at Shanghai Pulmonary Hospital between May 2018 and December 2024. Objective cognitive status was assessed using the Chinese versions of the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA), and total scores and subscores for each cognitive domain were calculated for each patient. We summarized the baseline characteristics, relevant laboratory tests, recurrence, and risk stratification features of the PE patients, compared the total and sub-item scores of the MMSE and MoCA, performed univariate and multivariate logistic regression analyses, and employed a Cox proportional hazards model to analyze prognostic factors in the PE cohort.ResultsPulmonary embolism patients had significantly lower total MMSE and MoCA scores than healthy controls, with declines across sub-items of orientation, Attention/Calculation (A&C), Visuospatial transformation (V-S total), and Delayed recall, indicating widespread cognitive impairment; patients with high risk and recurrence had even lower MMSE and MoCA scores (p < 0.05). Kaplan-Meier (KM) analysis demonstrated that patients with lower scores had higher recurrence rates and higher PE risk stratification. The ROC curve indicates that combining MMSE < 27.5 and MoCA < 25.5 can significantly improve the predictive efficacy for the occurrence of PE.ConclusionA significant decrease in the MMSE and MoCA cognitive function assessment scales is associated with a higher occurrence of PE and worse disease prognosis. Therefore, it is necessary to conduct cognitive function screening for patients with pulmonary embolism and to intervene as early as possible. Moreover, this finding further suggests that patients with PE constitute a potentially important group for cognitive rehabilitation, providing a valuable reference for the screening of populations in need of neurorehabilitation.